THE ROLE OF CADRES IN PROMOTING THE PARTICIPATION OF MOTHERS' TODDLERS IN THE INTEGRATED HEALTH CENTER OF KAMPUNG BARU VILLAGE, PASAR REBO SUBDISTRICT, EAST JAKARTA - Siti Fatimah, Okta Zenita; Hidayah, Seventina Nurul (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2024)
The Integrated Health Center is a community-based health initiative that aims to empower and facilitate the community's access to essential health services to reduce maternal mortality rate (MMR) and infant/child mortality rate. However, there is a need to increase the number of visits from mothers with toddlers to the Integrated Health Center, aiming for a 41% participation rate. This study seeks to investigate the role of cadres in promoting the involvement of mothers' toddlers in the Integrated Health Center program and to identify the factors that impact their participation rate. Conducted using a qualitative approach with a case study design and purposive sampling focusing on cadres, the data was gathered through in-depth interviews and focus group discussions (FGD), utilizing source and method triangulation for comprehensive insight. The findings indicate that cadres in the community serve as motivators, educators, and health service providers. They can recognize needs, address barriers, and facilitate the provision of health services. In addition to the cadres at the Integrated Health Posts (Posyandu), factors such as education level, economic status, and accessibility to health facilities play a role in the participation of mothers with toddlers in the Posyandu program. This research underscores the essential role of Posyandu cadres in encouraging the engagement of mothers with toddlers.